Temperature and stopover duration carry-over to affect Arctic arrival timing and breeding success in the cackling goose (Branta hutchinsii) - Bani Assadi, Saeedeh; Baldwin, Frank; Neufeld, Leanne; Fraser, Kevin C. (Frontiers in Ecology and Evolution, 2025)
Arrival timing in spring may be mediated by conditions experienced during migratory stopovers or staging areas, but our knowledge about their impact on migration timing and reproduction is limited. We explored the role of stopover duration on spring migration timing and successful incubation in cackling geese (Branta hutchinsii), which breed at high arctic latitudes where climate change effects are more pronounced. To track migration phenology and incubation duration, 236 light-level geolocators were deployed on cackling geese during the breeding period at Baffin Island, Nunavut, Canada between 2016 and 2018. Using data available for spring migration in the year following tag deployment (25 tags retrieved), we found that most geese had long, coastal stopovers (8–39 days) before crossing Hudson Bay on the last leg of their spring migration to their Baffin Island breeding area. We show that longer stopover durations at these Hudson Bay Lowland sites were associated with successful completion of incubation (a proxy for breeding success). Although spending more time at the stopover led to a later arrival date at the breeding ground, longer stopovers may increase the energy stores necessary for reproduction in these capital breeders. Stopover duration did not influence the incubation interval (number of days between arrival date at the breeding ground and start of incubation). Lastly, we found that the temperature at stopovers influenced migration timing, with higher temperatures resulting in earlier arrival at the breeding ground. Overall, our results demonstrate that conditions and behaviour at distant stopovers (1700–3000 km away) have important influence on timing and breeding success once birds arrive at their Arctic breeding sites. Therefore, our understanding of climate change impacts on these Arctic-breeding geese must also include the influence of en route conditions